Il Fondo Edifici di Culto. Tutela, valorizzazione e sviluppo sostenibile (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Brevi cenni introduttivi - 2. Il Fondo Edifici di Culto: struttura e patrimonio - 3. La missione del Fondo Edifici di Culto - 4. Conclusioni.Worship Buildings Fund. Protection, promotion and sustainable developmentABSTRACT: In the XIX century (mainly dating to the Sixties), laws were enacted for the secularization of all the religious assets. In order to protect, maintain and run this extremely rich, diversified and priceless estate, a Worship Buildings Fund (called Fondo Edifici di Culto = FEC) established by Law no. 222 (1985). Its holdings include many worship buildings (about 840 churches, abbeys, monasteries and convents), sacred objects, artworks, museums, archaelogical sites, book collections; as well as non-religious buildings (farms, schools, barracks and so on), and protected natural areas. Therefore FEC’s purposes need a renewed attention. A new governance will help to achieve the double goal, that is to administer faithfully the policies and objectives which best fulfill the needs, concerns and interests of this precious heritage and to support sustainable development.